IMPLEMENTASI ALGORITMA CLUSTERING DAN ANALITYCAL HIERARCHY PROCESS UNTUK MENENTUKAN PESERTA LATIHAN DASAR ORGANISASI KEMAHASISWAAN TERBAIK - Istiqomah Sumadikarta; Muhamad Bayu (JURNAL SATYA INFORMATIKA, 2021)
In a training activity, a strategy is needed to form groups and assess the best participants. Also like the Student Organization Basic Training (LDOK) at Satya Negara Indonesia University or elsewhere, good group division will increase the competitiveness of each group. Personality theory and the K-Mean method can provide options for forming training groups with equal distribution of participants' characters. With a balanced competition, it is hoped that the scores achieved by the participants can be optimal in each group. Selection of the best participants using the Analytical Hierarchy Process (AHP) method can be used for this purpose by determining the level of importance of each activity being assessed. The results of this study indicate that these two methods can be used as an option by the implementing committee to optimize the results of the training activities .